A comprehensive evaluation of cost-effective forged and aged β-type Ti–14Mn–Zr alloys with variable Zr content for biomedical implant applications - Ahmed H. Awad; Ahmed W. Abdelghany; Matias Jaskari; Antti Järvenpää; Mohamed Abdel-Hady Gepreel (Journal of Materials Research and Technology, 2025)
This study investigates the influence of Zirconium (Zr) content, hot forging, and aging treatments on the microstructure, mechanical properties, magnetic response, and biological performance of Ti–14Mn-xZr (x = 0, 3, and 6 wt%) alloys. Forging at 900 °C with ∼45 % reduction followed by water quenching induced slip-dominated plastic deformation, confirmed by EBSD analysis showing deformation bands, substructures, and dislocation accumulation.EBSD analysis revealed significant dislocation accumulation and stored energy, with weighted average geometrically necessary dislocation (GND) densities of approximately 2.71 × 1014 m−2 in Ti–14Mn–0Zr alloy and 2.45 × 1014 m−2 in Ti–14Mn–6Zr alloy. The EBSD images show several features related to the deformation bands and can be related to dynamic recrystallization, intersecting, and branching. The annealed Ti–14Mn–6Zr alloy exhibited the lowest Young's modulus of 106.2 GPa due to high β-phase stability and a single-phase structure. Forging followed by ageing at 700 °C improved tribological performance, yielding the lowest wear rate (3.61 μm/km/N) and coefficient of friction (0.43), with worn surfaces displaying characteristic features such as parallel grooves, debris accumulation, and wear craters. Biological testing showed that the previously mentioned alloy also exhibited the highest cell viability, attributed to its enhanced hydrophilicity and surface chemical stability. These findings suggest that the aged Ti–14Mn–6Zr alloy offers a favorable combination of mechanical integrity, wear resistance, and biocompatibility for long-term biomedical applications.